Strategi Pengembangan Usaha pada Industri Kayu Gergajian Melalui Pendekatan SWOT dan IFAS-EFAS Analysis - Mariaty Bintang Arthatama; Risma Fitriani (Peneliti.net, 2022)
The wood processing industry in Indonesia is a barometer of improvement in the national economy and a key factor in efforts to increase state revenues from the forestry sector. The purpose of this research is related to the work activities and productivity of a company that is needed and to find out strategies that can advance the company for the better in the future. In this study, the methods used were IFAS-EFAS analysis and SWOT analysis with interviews and questionnaires. The main strength of Cv. Cahaya Sawmill is a wide distribution network of 0.52. The main weakness of the company is that the warehouse is not too wide for product placement as much as 0.16. The main opportunity is the development of increasingly sophisticated technology by 0.48. The main threat Cv. Cahaya Sawmill is a bargaining power of 0.48 suppliers. From the results of data processing, it can be concluded that the strategies that can be carried out on Cv. Cahaya Sawmill is a SWOT strategy to penetrate the market, take advantage of technological developments, improve branding, make investments, create an integrated system, look for alternative warehouse locations, take advantage of business relationships, offer products, and improve company systems.